Data for the paper "Pattern Recognition of Barely Visible Impact Damage in Carbon Composites using Pulsed Thermography" - Zhao, Yifan; Addepalli, Pavan (Cranfield University, 2021)
Please find the attachment.
Keywords: 'NDT'; 'Image processing'; 'Feature extraction'; 'Artificial intelligence'; 'CFRP'; 'Signal Processing'